A recurrence-free survivor with chemotherapy-refractory small cell lung cancer after pneumonectomy: A case report and review of the literature. Issue 47 (November 2017) - Pan, Yong; Kong, Feng-Wei; Wang, Heng; Wang, Xiang; Zhang, Hui; Wu, Wen-Bin; Zhang, Miao
Abstract: Rationale: The optimal therapeutic regimen for chemotherapy-refractory and node-positive small-cell lung cancer (SCLC) is criticizable for the lack of evidence. Patient concerns: A patient with locally advanced SCLC was insensitive to the first-line chemotherapy of etoposide, irinotecan, and cisplatin. Diagnoses: The patient was diagnosed as SCLC with mediastinal lymph node metastasis by pathological staining. Interventions: Salvage pneumonectomy and systematic lymph node dissection combined with oral apatinib and mediastinal radiotherapy were performed for him. Outcomes: The patient survived for more than 2 years without recurrence after the operation and adjuvant therapy. Lessons: For patients with chemotherapy-resistant but resectable SCLC, a timely resection combined with postoperative radiotherapy and apatinib might be effective.